PENGEMBANGAN TEKNOLOGI PENGOLAHAN DAN PENGEMASAN, SERTA PEMASARAN PRODUK STIK NANAS DAN STIK UBI JALAR PADA KELOMPOK USAHA AL ZEESHAN DESA PUTAK, KECAMATAN GELUMBANG, KABUPATEN MUARA ENIM - Merynda Indriyani Syafutri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Pineapple and sweet potato are agricultural products in Putak Village. In Putak Village, a business group for processing pineapple sticks and sweet potato sticks had been formed. The purpose of the activity was to provide guidance and assistance in the development of processing technology, packaging, and marketing of pineapple sticks and sweet potato sticks products. The methods were counseling and providing material about the potential of various sweet potato varieties to be processed into stick products, and packaging technology. This activity was carried out through training, practice, demonstration, and guidance on processing, packaging, and marketing. The participants were very enthusiastic and active. The results of the activity showed that the sweet potato sticks product had been developed into 3 types, namely purple, yellow, and white sweet potato sticks. The pineapple sticks and sweet potato sticks were better, and packaged using standing pouch clips and PP plastic with more attractive labels. The product of pineapple sticks and sweet potato sticks had been registered in Dinkes of Muara Enim Regency to get a P-IRT certificate, with the business name "Al Zeeshan". The products of pineapple sticks and sweet potato sticks had also been promoted and marketed at several exhibitions and minimarkets.